β1-adrenergic blockade augments pulsatile PTH secretion in humans - Schmitt, Claus P.; Obry, Jennifer; Feneberg, Reinhard; Veldhuis, Johannes D.; Mehls, Otto; Ritz, Eberhard; Schaefer, Franz (Journal of the American Society of Nephrology, 2003)
Pulsatile peptide hormone secretion provides efficient control of specific end organ functions. To test the hypothesis that sympathetic neuronal activity drives synchronous pulsatile PTH release from the parathyroid glands, we investigated the acute effects of β1-adrenergic receptor blockade on PTH secretion patterns in a single-blinded study in nine healthy adults. Plasma PTH levels were determined at 1-min intervals. After a 75-min baseline period, seven subjects received a continuous intravenous infusion of the short-acting β1-adrenergic receptor blocker esmolol for 105 min. After a 30-min washout period, esmolol was infused for another 30 min. Two additional subjects were randomized to receive solvent infusions.
Gesehen am 13.01.2021